An Integral Analysis of Supplier Selection and Supplier Relationship of Tobacco and Sugar Industry in Bangladesh- A Case Study (International Journal of Scientific Research and Management (IJSRM), 2013)
Supplier relationship management is an imperative contributor to a company’s efficiency and is being viewed as strategic, process-oriented, cross-functional, and value-creating for buyer and seller. Supplier selection, one of the most important issues of a company, need to be systematically considered from the decision makers’ perspectives and a multi criteria decision problem and a model has been proposed by using Analytical Hierarchy Process. The evaluation criteria has been developed and used successfully in the proposed model. The design of supplier relationship management to facilitate supplier selection using an integrative case based on supplier selection to select the most appropriate suppliers together with their past performance records to identify preferred suppliers. This paper shows the benefits of good supplier relationship rather than a traditional one. It also focuses on the specifying sources, selecting suppliers, negotiating with supplier, buying raw materials and designing and supplying collaboration.